Translating Cultures: A Linguistic Reading of A Dream of Red Mansions - Wu, Jianshe (Meta, 2008)
AbstractThis paper attempts to present a contrastive analysis of sets of translation of the same work, in the same language but of different versions, from a linguistic perspective, by means of Motion event. In analyzing the same, we attach great importance to the source text effect as well as the translator effect on the target text.As suggested by Talmy (1985, 2000), different languages contain different systems of verbs of motion, which could be described by a universal pattern of its semantic elements: Figure, Ground, Motion, Path and Manner. Accordingly English and Chinese could be both classified as satellite-framed languages (the other alternative is verb-framed languages) (Talmy 2000). And in this wake, many researches flourish in different language contexts in hopes of validating the “linguistic relativity” hypothesis.However, up to now, a linguistic adoption of Motion event has not been found in analyzing the possible source and translator effects underlying the translation works in the same language but of different versions. In this view, this paper tends to utilize this semantic category to analyze the above-mentioned effects as represented in David Hawkes, John Minford, and Xianyi Yang and Galdys Yang, in the light of their respective translatings of A Dream of Red Mansions (or the Story of the Stone).